2012
DOI: 10.1038/ismej.2012.154
|View full text |Cite
|
Sign up to set email alerts
|

Microbial composition affects the functioning of estuarine sediments

Abstract: Although microorganisms largely drive many ecosystem processes, the relationship between microbial composition and their functioning remains unclear. To tease apart the effects of composition and the environment directly, microbial composition must be manipulated and maintained, ideally in a natural ecosystem. In this study, we aimed to test whether variability in microbial composition affects functional processes in a field setting, by reciprocally transplanting riverbed sediments between low-and high-salinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
83
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 54 publications
7
83
0
1
Order By: Relevance
“…This is consistent with other studies where microbial biomass influenced methane efflux and nitrification (Balser & Firestone 2005;Reed & Martiny 2013). These results can also be supported by Schimel (1995) as described above.…”
Section: Relationship Between Fungi and N 2 O Effluxsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with other studies where microbial biomass influenced methane efflux and nitrification (Balser & Firestone 2005;Reed & Martiny 2013). These results can also be supported by Schimel (1995) as described above.…”
Section: Relationship Between Fungi and N 2 O Effluxsupporting
confidence: 93%
“…Previous studies found that fungi were involved in denitrification processes by reducing nitrate or nitrite to N 2 O in freshwater sediments (Takaya 2009;Seo & DeLaune 2010;Mouton et al 2012;Reed & Martiny 2013;S anchez-Andrea et al 2012). In particular, cell-free nitrate reductase (Nar) and nitrite reductase (Nir) activities which also included a unique cytochrome P450 acted as nitric oxide reductase played important roles in the anaerobic denitrification process of fungi (Usuda et al 1995).…”
Section: Relationship Between Fungi and N 2 O Effluxmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbes catalyze most of the biological transformations of the major elements of life (7), and because of their sheer abundance they account for a large pool of elements in living matter (8). Furthermore, like plants and animals, microbial taxonomic composition varies over space (9,10), and this variation can influence ecosystem processes (11)(12)(13)(14). Thus, a consideration of microbial traits should improve efforts to connect biogeographic patterns and ecosystem processes (15).…”
mentioning
confidence: 99%
“…If a gene from a pathway was detected, we assumed the presence of the entire pathway in the organism. To compare the frequencies among the N pathways, we standardized for the number of genes (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in each pathway. Although metagenomic sequences provide a measure of a community's trait diversity (24), the presence of a trait does not indicate how it is being used in the community.…”
mentioning
confidence: 99%